PENGARUH DISKUSI KELOMPOK TERHADAP KEPATUHAN KONSUMSI TABLET TAMBAH DARAH DAN KADAR HEMOGLOBIN PADA SISWA PUTRI DI SMAN 1 SENDURO, LUMAJANG - Dwi Anisa Sukmawati; Ainul Yaqin Salam; Achmad Kusyairi (Health and Technology Journal (HTechJ), 2024)
Anemia is one of the health problems that still affects Indonesia. One of the causes of anemia is a lack of knowledge and iron supplement adherence, which can lead to anemia. This research aims to determine the effect of group discussion method education on iron supplement adherence and Hemoglobin levels in female students at SMAN 1 Senduro, Lumajang. This research was a quasi-experimental pretest-posttest quantitative with a non-probability total sampling technique. The sample used in this research was adolescent girls, with 41 students. Measurement of the level of adherence used the Morisky Medication Adherence Scale (MMAS-8) and given the intervention of pretest and post-test. Data was tested using the Wilcoxon Signed Rank Test. The results of this research showed that adolescents with iron supplement adherence before group discussions were in the low category 41 (100%). After the group discussion, the high category was 2 (4.9%), low 21 (51.2%); before the group discussion, the average Hb level was 10.65mg/dl; after the group discussion, the average Hb result was 11.37 mg/dl. The results of the Wilcoxon test obtained a p-value of 0.000 (p < 0.05), which means that there is a significant effect of the provision of education on group discussion methods in adolescent girls. An increase influenced the increase in hemoglobin levels in the consumption of blood supplement tablets in adolescent girls, showing active participation and changes from before and after the group discussion. Respondents who remained anemic after the group discussion were due to a lack of iron needs and a lack of knowledge of consuming nutritious food.